From data to Wisdom: Revolutionizing agricultural sustainability through knowledge management in Najaf, Iraq - Thamer Adheem Abed; Shahla Choobchian; Enayat Abbasi (Environmental and Sustainability Indicators)
The agricultural sector is confronting unprecedented challenges driven by climate change, resource scarcity, and increasing food demand. This study explores the transformative potential of knowledge management (KM) in agricultural organizations, highlighting its role in promoting sustainability and fostering innovation. Employing the Data-Information-Knowledge-Wisdom (DIKW) framework, the research reveals that significant gaps exist in processing information, effectively leveraging knowledge, and translating it into strategic wisdom for long-term decision-making. This study presents compelling evidence that KM plays a pivotal role in advancing social and economic sustainability, though environmental sustainability continues to pose significant challenges. A high path coefficient of 0.73 between the DIKW framework and sustainability outcomes underscores the strategic value of informed, knowledge-based decision-making. The findings call for the enhancement of information infrastructure, the institutionalization of knowledge-sharing mechanisms, and the thoughtful incorporation of wisdom into policy development. To foster a resilient agricultural ecosystem capable of adapting to climatic uncertainties, the study emphasizes the importance of integrating digital technologies, promoting participatory governance, and adopting evidence-based policymaking. This research offers a robust, hybrid KM model that synergizes conventional frameworks with AI-driven innovations, specifically tailored to the fragile agro-ecological setting of Najaf, Iraq, while providing scalable insights for similar semi-arid and conflict-prone regions around the globe.